Changements techniques et dynamique d’innovation agricole en Afrique Sahelienne: le cas du Zaï mécanisé au Burkina Faso et de l’introduction d’une cactée en Ethiopie - Danièle Clavel; Albert Barro; Tesfay Belay; Rabah Lahmar; Florent Maraux (VertigO)
In Africa, 45% of the land is located in regions where rainfed agriculture is weakened by recurrent droughts. In Burkina Faso, soil degradation can be limited by the Zaï technique, which is a very labour-intensive traditional, manual technique (300 h/ha). By mechanizing the operation it only takes 40 h/ha. Today, several hundred farms and craftsmen in around twenty villages in northern Burkina Faso are benefiting from the improved technique. A cactus (Opuntia ficus-indica Mill), which originates from Mexico, was accidentally introduced less than 20 years ago in the arid province of Tigray in northern Ethiopia. Within a very short time, ways of growing, using and processing the different products derived from Opuntia have been technically developed, leading to better human and animal nutrition, and income during lean periods (July-September). At the outset, this progress was initiated by local agricultural research, but it was rapidly boosted by multi stakeholder collaboration, notably involving users of the techniques, particularly farmers themselves. These two cases were presented at the AIDA conference (Agricultural Innovation in Dryland Africa) (http://inco-aida.cirad.fr ) held in Accra (Ghana), 22-24 January 2007, which enabled the first inventory of agricultural improvement case studies in Sahelian Africa. The main lesson learnt from the conference, illustrated by these two case studies, was that under conditions of considerable spatial and temporal variability in environmental and human factors, agricultural innovation is a dynamic, complex and interactive process and a complete break from the linear technology transfer approaches mostly taken in the last 40 years. Today, the methods and approaches whereby this complexity can be integrated are at the heart of the debate, so that technological improvements can be appropriated by the stakeholders, their impact increased, and their durability ensured in contexts with very little economic and climatic room for manoeuvre.